Brain unidentified bright objects ("UBO") in systemic lupus erythematosus: sometimes they come back. A study of microembolism by cMRI and Transcranial Doppler ultrasound. (February 2016) - Bortoluzzi, A; Padovan, M; Azzini, C; De Vito, A; Trotta, F; Govoni, M
Objectives: The objectives of this report are to assess the occurrence of microembolic signals (MES) detected by transcranial Doppler ultrasound (TCD) in systemic lupus erythematosus (SLE) patients with (NPSLE) and without (SLE) neuropsychiatric involvement, and to verify the correlation between MES, clinical characteristics, especially the patent foramen ovale (PFO), and the presence of punctuate T2-hyperintense white matter lesions (WMHLs) detected by conventional magnetic resonance imaging (cMRI). Methods: A TCD registration to detect MES from the middle cerebral artery was carried out in SLE and NPSLE patients after exclusion of aortic and/or carotid atheromatous disease. In all patients conventional brain magnetic resonance imaging (cMRI) and transesophageal echocardiography were performed. Patients were stratified in two groups, with and without WMHLs, and compared. Results: Twenty-three SLE patients (16 NPSLE and seven SLE) were enrolled in the study. Overall MES were detected in 12 patients (52.1%), WHMLs were detectable in 15 patients (13 NPSLE and two SLE) while eight patients had normal cMRI (three NPSLE and five SLE). Matching TCD ultrasound and neuroimaging data, MES were detected in 10 (nine NPSLE and one SLE) out of 15 patients with WHMLs and in only two out of eight patients (two NPSLE and six SLE) with normal cMRI, both with NP involvement. A PFO was confirmed in all cases of MES detection. Conclusion: MES are frequent findings in SLE patients, especially in those with focal WMHLs detected by cMRI and correlating with PFO. These findings should be taken into account and suggest caution in the interpretation of cMRI pictures along with a careful evaluation of MES in patients with cMRI abnormalities that should be included in the workup of SLE patients.